Real-time quantitative PCR-based system for determining transgene copy number in transgenic animals. (October 2004) - Ballester, Maria; Castelló, Anna; Ibáñez, Elena; Sánchez, Armand; Folch, Josep M.
In this paper, we describe a rapid and accurate real-time quantitative PCR-based system to determine transgene copy number in transgenic animals. We used the 2 −ΔΔCt method to analyze different transgenic lines without the requirement of a control sample previously determined by Southern blot analysis. To determine the transgene copy number in several mouse lines carrying a goat β-Lactoglobulin transgene, we developed a TaqMan ® assay in which a goat genomic DNA sample was used as a calibrator. Moreover, we used the glucagon gene as a reference control because this gene is highly conserved between species and amplifies with the same efficiency and sensitivity in goat as in mouse. With this assay, we provide an alternative simple method to determine the transgene copy number, avoiding the traditional and tedious blotting techniques. The assay's discrimination ability from our results is of at least six copies and, similar to the limitations of the blotting techniques, the accuracy of the quantification diminishes when the transgene copy number is high.